Pengaruh Aktivitas Fundraising Terhadap Minat Muzzakki Membayar Zakat Di BAZNAS Kabupaten Sorong: Studi Kasus Kelurahan Malawili - Junita Junita (Prodi Ekonomi Syariah IAIN Sorong, 2022)
The purpose of this study was to determine the effect of fundraising activities on muzakki's interest in paying zakat in Baznas, Sorong Regency. This research uses quantitative methods with a descriptive approach. The population in this study was muzakki who paid zakat in BAZNAS Sorong Regency, especially Malawili village, as many as 124 muzzaki. However, this study was only carried out on 55 muzakki as samples in the study. Data analysis was carried out using the help of SPSS 28. To achieve the objectives of this study, research instrument tests (validity test and reliability test), normality, linearity, classical assumption test, simple linear regression, t test hypothesis test and determination coefficient test are used. In accordance with the significance test criteria on the linearity test, f calculates > f table, then H0 is rejected and Ha is accepted. In addition, the same result was also obtained after conducting a t-test which said that t table = 2.005 < t count = 3.379, then it means that H0 is rejected. Thus, this hypothesis states that fundraising activities on muzakki's interest in paying zakat in BAZNAS Sorong Regency have a positive effect on muzakki's interest in paying zakat in BAZNAS Sorong Regency. From the results of the presentation above, it has a positive influence on muzakki and mustahik. The positive influence for muzakki is that there is an official, trustworthy, and trustworthy amil zakat institution. Meanwhile, it has a positive effect on mustahik in the form of welfare of the poor.